2020
DOI: 10.5114/pm.2020.97867
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestation and its management in postmenopausal women: an integrated review

Abstract: Postmenopause is a phase of life which leads physical and emotional instability from multiple health related issues. Oral health in this stage of life is also compromised. Oral health has an impact on general wellbeing of the individual as oral cavity is commonly act as a mirror to general health. Menopause is phase in a woman’s life when menstrual cycles cease by reduced secretion of the ovarian hormones, such as estrogen and progesterone. This review article has emphasized on the diverse oral presentations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 26 publications
0
27
0
6
Order By: Relevance
“…Based on previous clinical studies, it is generally believed that mental stress is one of the possible risk factors for the development of OLP ( 6 ). A previous study showed that in postmenopausal women, stress could lead to anxiety and depression, which are common reasons of lichen planus ( 7 ). A study showed that 48% of the 274 OLP patients had mental problems, and anxiety, depression and stress existed in 45% of these OLP patients with mental problems ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous clinical studies, it is generally believed that mental stress is one of the possible risk factors for the development of OLP ( 6 ). A previous study showed that in postmenopausal women, stress could lead to anxiety and depression, which are common reasons of lichen planus ( 7 ). A study showed that 48% of the 274 OLP patients had mental problems, and anxiety, depression and stress existed in 45% of these OLP patients with mental problems ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Visualizando os riscos dos pacientes osteoporóticos se faz necessário entender sobre o desenvolvimento da doença a fim de atingir o mecanismo fisiopatológico e minimizar as suas repercussões. Alguns artigos abordaram indiretamente a osteoporose através desses fatores de risco, sendo eles: mulheres menopausadas, diabetes mellitus e a deficiência de vitamina D (Jagelaviciene et al, 2018;Sen et al, 2020;Izuora et al, 2020;Wang & McCauley, 2016;Tanaka et al, 2020).…”
Section: Discussionunclassified
“…Segundo, Sen et al (2020) as principais manifestações clínicas em mulheres menopausadas são a xerostomia, síndrome da boca ardente, periodontite, gengivite, neuralgia do trigêmeo, distúrbios de mucosa e a osteoporose. A explicação para isso se dá através da baixa produção de estrogênio após a menopausa, estimulando a produção de substâncias inflamatórias (interleucinas, fator de necrose tumoral alfa, granulócitos, fator estimulador de colônias, etc.)…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Around the same time, changes in oral health are also common as teeth and gums become more susceptible to disease, which can lead to inflammation, pain, bleeding, and eventually lost or missing teeth. Estrogen therapy was shown to be effective in reducing tooth and gum diseases in postmenopausal women [ 138 , 139 , 140 ]. This protective role is lost in older adults or postmenopausal women due to decreased levels of endogenous sex hormones among COVID-19 patients [ 87 , 88 ].…”
Section: Potential Drugs For Fighting Sars-cov-2 Infection and Thementioning
confidence: 99%